Older age is a protective factor for academic achievements irrespective of treatment modalities for posterior fossa brain tumours in children. - Jarmila Kruseova (PLoS ONE, 2020)
The treatment of children with posterior fossa brain tumours (PFBT) impacts their long term functional and imaging outcomes. This study aimed to evaluate academic achievement correlated with long-term sequelae after different PFBT treatment modalities. The study cohort consisted of 110 survivors (median age at diagnosis 10.1 years and median time of follow up 13.2 years) who completed hearing questionnaires, neurological assessment and MRI of the brain ≥5 years after the end of treatment. There were three treatment groups. A cisplatin group which underwent cisplatin chemotherapy, radiotherapy and surgery (medulloblastoma N = 40), a radiotherapy group which underwent radiotherapy and surgery (astrocytoma/ependymoma N = 30), and a surgery group (astrocytoma N = 40). Academic achievement was correlated to the age at diagnosis, ototoxicity, Karnofsky score (KS), and MRI findings (Fazekas Score (FS)- treatment related parenchymal changes). For a modelled age at diagnosis of five years, the cisplatin group had lower academic achievements compared to the radiotherapy (p = 0.028) and surgery (p = 0.014) groups. Academic achievements evaluated at a modelled age of 10 years at diagnosis did not significantly differ among the treatment groups. The cisplatin group exhibited a higher occurrence of ototoxicity than the radiotherapy (p<0.019) and surgery groups (p<0.001); however, there was no correlation between ototoxicity and academic achievements (p = 0.722) in older age at diagnosis. The radiotherapy group exhibited lower KS than the surgery group (p<0.001). KS significantly influenced academic achievements in all groups (p<0.000). The cisplatin group exhibited higher FS than the surgery group (p<0.001) while FS did not correlate with academic achievement (p = 0.399). Older age is a protective factor for academic achievements irrespective of a treatment modality.